Vital Functions Contribute to the Spread of Extracellular Fluids in the Brain: Comparison Between Life and Death - Piotrowska, Alina; Winter, Karsten; Carare, Roxana O.; Bechmann, Ingo (Frontiers in Aging Neuroscience, 2020)
Vascular pulsations, contractions of vascular smooth muscle cells and breathing have been reported to foster movement and clearance of interstitial and cerebrospinal fluids from the brain. The aim of this study was to estimate the contribution of these vital functions. We compared the spread of an injected hydrophilic tracer (Fluoro-Emerald, a 10kDa fluorescein-coupled dextran amine) in the brains of live anesthetized and sacrificed rats at 30 and 90 min after injection. To determine the overall pattern of distribution of tracers, we created 3D-reconstructions of the horizontal transections of the whole brain. Immunofluorescence staining with laminin and collagen IV was performed to determine the pattern of distribution of tracer in relation to the cerebrovascular basement membranes. We found that diffusion was widely restricted to the periventricular region in sacrificed rats with no spread to the contralateral hemisphere, while the bulk flow occurred along the vasculature and reached the surface and the contralateral hemisphere as soon as 30 min after injection in live anesthetized animals. The tracer appeared to be localized along the vascular basement membranes and along fiber tracts as reported previously. Thus, our data indicate that vital functions are essential for the remote movement of extracellular fluids within the cerebral parenchyma.